Peran Metode Montessori dalam Meningkatkan Kemandirian, Keterampilan Komunikasi, dan Kecerdasan Emosi Anak Kelas Nursery - Shianny Shianny; Sri Lanawati Raharja (Syntax Corporation Indonesia, 2024)
Independence, communication skills, and emotional intelligence are very essential competencies for students in their lives. This study aims to find and analyze differences in independence, communications skills, and emotional intelligence of lower level students using the Montessori method. This research was conducted during March 2024 with six meetings. The subjects in this research were 13 students. The type of research used is quantitative research with experimental methods with pre-experimental design types, one group pre-test – post-test. The research instrument used is a rubric for all validated variables. Pre-test and post-test data are tested using n-gain and t-test. The results of the independence hypothesis test show the acquisition of n-gain results 0,36 and t-test 21%; communication skills show the acquisition of 0,46; emotional intelligence shows the acquisition of 0,23. From the results obtained, it can be conluded that there are differences where students experience improvements in the three variables mentioned using the Montessori method.